Розробка автоматизованої охоронної системи контролю доступу до приміщення лабораторії - Максименко, М. А. (ХНУРЕ, 2021)
In this work, a block diagram for an automated security system has been developed. Access control in the premises will be provided by motion sensors, an electronic lock, and sound indication. There is also a block diagram for connecting the elements of the security system.
Keywords: охоронна система; контроль доступу; приміщення лабораторії